The Significance and Performance of REIT in a mixed-asset portfolio in Four European Countries - THIEBAUT, Alexandre (2021)
Real Estate Investment Trust (REIT thereafter) was first developed in the 1960s in the USA. Even though in 1969 REIT legislation is passed in Netherlands, the European REIT markets started to be significant only from the 20 past years. Nowadays, the four biggest European REIT markets are United-Kingdom, France, Spain and Belgium. This paper assesses the performance and the diversification benefit of the four European REIT market stated above. The analysis is based on the 10 past years from 2011 to 2021 with a focus on the effect of the Covid crisis. Results from the different analysis have shown that REIT’s diversification benefit is different for each country and vary over time. The risk-performance adjusted also differ both between countries and time period. In each country, the covid crisis negatively impacted each REIT’s performance. However, some markets were more resilient than others. Other studies could be undertaken to look closely at the different legislation or other REIT’s fundamentals that could explain the different performances.